Analytical study of some materials used to reduce carbon dioxide CO2 emissions - Khellou, Ikram; Rahmania, Rayane; Chetti, Fatima Zohra; Chetti, Chahinez; Berramdane, Hassna (Echahid Hama Lakhdar University of Eloued, 2023)
"The proposal focuses on using calcium-based compounds to capture and store carbon dioxide (CO2) from the atmosphere. This is crucial due to the rising CO2 levels, which pose a significant climate challenge. The key objective is to find an effective and locally available method for this purpose. The proposal suggests identifying suitable calcium sources, developing efficient capture technologies, and implementing cost-effective storage strategies. Heat treatment is utilized to obtain pure and efficient calcium oxide from calcium and carbon, with oxygen being the most abundant element. Infrared spectroscopic (FTIR) analysis confirms the presence of calcium, oxygen, and carbon, while XRD patterns indicate the existence of well-crystallized calcite (CaCO3). Utilizing calcium-based compounds offers a locally available and effective solution for capturing and storing CO2, thereby mitigating the impacts of climate change. Continuous innovation, investment, and collaboration are essential for finding sustainable solutions to global challenges and preserving our planet for future generations. " "يركز هذا الاقتراح على استخدام المركبات القائمة على الكالسيوم لالتقاط وتخزين ثاني أكسيد الكربون الموجود في الغلاف الجوي, وهذا الأمر بالغ الأهمية نظرا لمستويات ثاني أكسيد الكربون التي تسبب. الهدف الرئيسي هو إيجاد طريقة فعالة ومتاحة محليا لهذا الغرض يقترح الاقتراح تحديد تقنيات الالتقاط الفعالة المناسبة والتنفيذ الفعال من حيث التكلفة واستراتيجيات التخزين. المعالجة الحرارية للحصول على الكالسيوم النقي والفعال لأكسيد الكالسيوم والكربون والأكسجين. تحليل نقل وتحويل الأشعة تحت الحمراء قدمت المركبات الأساسية الأكسجين والكالسيوم والكربون, حيود الأشعة السينية تشير الى أن أسيتات الكالسيوم متبلور جيدا. الاستثمار والتعاون ضروريان لإيجاد حلول مستدامة للتحديات العالمية والحفاظ على كوكبنا للأجيال القادمة."
مذكرة ماستر هندسة كيميائيةDes thèses génie chimique
Keywords: carbon dioxide capture, calcium-based compounds, heat treatment, Infrared spectroscopic (FTIR), calcium acetate, XRD.; التقاط ثاني أكسيد الكربون, مركبات الكالسيوم, المعالجة الحرارية,طيفي الأشعة تحت الحمراء,خلات الكالسيوم,حيود الأشعة السينية